PENGARUH KOMUNIKASI DAN ETOS KERJA TERHADAP KEPUASAN KERJAANGGOTA POLRI BAGIAN MEKANIK PADA SUBDIT FASHARKAN PADA DITPOLUDARA KORPOLAIRUD BAHARKAM POLRI - Asep Subur; Yudhi Ariyanto (Sekolah Tinggi Manajemen IMMI, 2018)
The study entitled “The Influence of Communication and Work Ethics on Job Satisfaction of Polri Members of the Mechanic Section in the Fasharkan Sub-Directorate of the Directorate of Polriud of Baharkam Polri aims to get an overview of the influence and contribution of work ethics in realizing Member job satisfaction. This research was carried out using primary and secondary data from the Fasharkan Sub-Directorate of Polriud of Baharkam Police. The results of the study show that together communication and work ethic make a significant contribution in realizing Member job satisfaction. Partially only communication that contributes significantly, while work ethic has no influence. However, besides continuing to improve constructive communication, the work ethic must be cultivated by instilling awareness that work is trust, worship, grace and work is an honor.